PROCESS OPERATION OF LOCAL SELF-GOVERNMENT - Jekić, Cviko (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2015)
Local self-government in the region, characterised by its bureaucratic and hierarchical structure, insufficient expertise, lack of knowledge and excessive procedures used in its operation, is simply unable to cope with the creation of a new society and an adequate economic environment. The lack of customer and target orientation, low level of understanding and poor utilisation of the principles and mechanisms of good governance (customer orientation, efficiency, participation, impartiality, transparency, professionalism, etc.) results in poor quality of service. It seems necessary to conduct major alterations and to create new local government or administration that would perform basic administrative functions in line with the growing requirements of citizens – users or customers and that would develop a community that would be competitive, both as a place to live and as a place to do business.